Relative Importance of Locality and Seed Origin in Determining Wood Quality in Teak - Purkayastha, S. K.; Satyamurthi, K. R. (Indian Forester, 1973)
Analysis of the data on wood specific gravity and rate of growth of teak from two seed origins grown at South Coimbatore and Nilambur showed that locality has a highly significant effect while the variation due to seed origin was not significant.